Gross and Morphometric Anatomy of the Male Reproductive System of Bats (Eidolon helvum) - A. Danmaigoro; J. E. Onu; M. L. Sonfada; M. A. Umaru; S. A. Hena; A. Mahmuda (Veterinary Medicine International)
The present study aimed at examining the gross and morphometry of the reproductive tract of the male bats (Eidolon helvum). Thirty male bats (adults n=17 and juveniles n=13) were captured using net, weighed, aged using relative ossification of the wing bone, and dissected for gross examination. Morphologically, the mean body weight and forearm length in both adults and juveniles were 235.31±6.30 g, 12.14±0.19 cm and 69.54±7.68 g, 7.77±0.29 cm, respectively. The testicles were completely descended in adults with the penis projected cranially. The epididymides were found at the median border of the testis and continues as vas deferens. No significant differences (P>0.05) were observed between right and left testicular weights in both adults and juveniles and also in lengths of different parts of the reproductive segments in both age groups assessed, respectively. This work has documented the gross anatomy of the male reproductive tract in bats. Ultrastructure and histochemistry are recommended for further insight into the reproductive biology.